The Effect Of Service Quality And Price On Customer Satisfaction Of Mineral And Coal Mining Consulting Services At Pt Allsys Solutions - Gemina, Dwi; Silaningsih, Endang; Tjahja Andari, Titiek; Kartini, Tini; Julaiha, Siti (International Journal of Science, Technology & Management, 2023)
The rapid development of business in the era of globalization causes competition between companies to be tighter, so various efforts must be made in order to attract the attention of consumers from competitors. This study aims to determine and analyze service quality and price both simultaneously and partially on PT Allsys Solutions customer satisfaction. The sampling amounted to 92 consumers with a saturated sampling technique in which all members of the population were sampled. This questionnaire is tested with validity tests, reliability tests and also classical assumption tests. The results of the test are valid, reliable and can be used for regression data. The analytical methods used in this study are descriptive and verifiative methods with a quantitative approach. The results showed that the variables of service quality and price had a direct and positive effect on PT Allsys Solutions customer satisfaction. The result of the R (square) determination test is 40.61% while the remaining 59.39%. The relationship between service quality and price has a strong relationship with the result of a correlation coefficient of sort. 0.637.